PENINGKATAN PENGETAHUAN KEPADA MASYARAKAT DALAM MENGENALI KEJADIAN HAPPY HYPOKSIA - Pertiwi Perwiraningtyas; Ani Sutriningsih; Wahyu Dini Metrikayanto (Jurnal LENTERA, 2022)
Happy hypoxia is an asymptomatic condition where oxygen saturation decreases<90% in Covid-19 patients. However, many people do not know the signs andsymptoms of happy hypoxia. Preventive measures are needed to prevent theworst possible occurrence of happy hypoxia, one of which is health education.The purpose of this community service activity is to make the community awareof the occurrence of happy hypoxia. The activity was carried out for one day for18 families of patients in the emergency room at Panti Waluya Sawahan Hospital,Malang. The patient's family is given a pre-test to measure the understanding ofhappy hypoxia, then given health education, then given a post-test sheet. Theresults obtained in the form of increasing knowledge from the less to goodcategory. This health education activity is included in preventive efforts so thatthe public can recognize the occurrence of happy hypoxia to minimize themortality rate of Covid-19 patients.